Review of professional values, self-efficacy and job satisfaction of obstetric nurses across job-related challenges - Li, Changhong; Mohd Arifin, Siti Roshaidai; Ahmad, Norfadzilah; Hashi, Abdurezak Abdulahi; Farooq, Umar (Épanoui Publications, 2020)
The purpose of this review was to examine articles related to professional values, self-efficacy and job satisfaction of obstetric nurses across job-related challenges across different countries and cultures, as well as to identify specific studies that have been carried out exclusively in China. The review was undertaken in two stages, an initial review and an updated review. At both stages systematic literature searches of online databases were performed to identify articles on the professional values, self-efficacy and job satisfaction of obstetric nurses across job-related challenges. A total of 27 articles concerning research were included in the final analysis.